Nostalgic Marketing Strategies and Customers Repurchase Intentions - Ikpeazu, Peter; Ogbeide, Darlington (Journal of Entrepreneurship & Business, 2026)
Purpose: This study aims to examine the influence of nostalgic marketing strategies on customer repeat purchase in the fast-moving consumer goods sector, with a particular focus on Indomie noodles in Asaba, Delta State, Nigeria. Specifically, it investigates the effects of nostalgic emotions, nostalgic brand positioning, nostalgic brand equity, nostalgic sensitivity, and nostalgic advertising on repeat purchase behavior. Method: A cross-sectional survey was conducted, targeting 893 management-level employees and product distributors from selected FMCG firms. Using the Research Advisor’s sampling table, a sample size of 564 respondents was selected. Data were collected using structured questionnaires adapted from validated instruments and analyzed with SPSS (v. 26) and SmartPLS 3. Result: The findings revealed that nostalgic brand positioning, nostalgic brand equity, nostalgic sensitivity, and nostalgic advertising have significant positive effects on customer repeat purchase. In contrast, nostalgic emotions showed a positive but insignificant effect. The regression model confirmed nostalgic marketing as a strong predictor of repurchase intentions in the FMCG sector.